Refractory diseases and the, “opacity of the right to health” - Alves, Cândice Lisbôa; Resende, José Renato Venâncio (Argumentum, 2020)
Although public health has been enshrined as a fundamental right since 1988, there are signs, in Brazil, of a mismatch between the deontic and ontic worlds regarding the subject in question; and one of the reasons are the historical, semantic and minority-related vulnerabilities. This article problematizes the statement of article 196 of the Constitution, seeking to incite reflection on the reasons for its non-implementation. The working hypothesis is that the idea of ​​traditional equality hinders the realization of minority rights. It is bibliographic research, using an argumentative method. The working hypothesis is confirmed as striving for a new meaning of public health.